Nehiyawak (Cree) women's strategies for aging well: community-based participatory research in Maskwacîs, Alberta, Canada, by the Sohkitehew (Strong Heart) group - Luwana Listener; Sue Ross; Richard Oster; Bonny Graham; Seth Heckman; Cora Voyageur (BMC, 2023)
Abstract Background The Sohkitehew (Strong Heart) Research Group, which included an Elders Advisory Committee of seven Nehiyawak (Cree) women, set out to bring Maskwacîs community members together to understand Nehiyawak women's experiences of "aging well". The goals of this research were to generate information honouring Indigenous ways of knowing, and gather strengths-based knowledge about aging well, to help Maskwacîs, women maintain wellness as they age. Methods We facilitated qualitative Sharing Circles in three different settings in Maskwacîs. Discussions were prompted using the four aspects of the self, guided by Medicine Wheel teachings: Physical, Mental, Emotional, Spiritual. Detailed notes were recorded on flip charts during the discussions of each Sharing Circle. Data were analysed using descriptive content analysis to identify practical strategies for aging well. Results Thirty-six community members attended one or more Sharing Circle. Strategies included: Physical-keeping active to remain well; Mental-learning new skills to nourish your mind; Emotional-laughing, crying, and being happy; Spiritual-practicing Nehiyawak traditional ways. Participants commented that balancing these four aspects of the self is necessary to achieve wellness. Following the analysis of the Sharing Circle comments, three community feedback sessions were held to discuss the results in the wider community. These strategies were formatted into a draft booklet which incorporated Cree language, and archive photographs of Maskwacîs women and families. Conclusions The Nehiyawak Sharing Circles identified practical strategies that help women to remain well as they age. This positive approach to aging could be adopted in other Indigenous and non-Indigenous communities.